1980
DOI: 10.1071/bi9800557
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Ultradian and Circadian Rhythms in the Concentration of Cortisol and Prolactin in the Plasma of Dairy Cattle

Abstract: This experiment analysed the circadian and ultradian pattern of secretion of cortisol and prolactin in cattle, and from this a meaningful sampling technique for these hormones has been suggested.Two Friesian and two Jersey heifers, non-pregnant and 18 months of age, were bled (2 ml blood) every 10 min for 24 h via an indwelling jugular cannula inserted 6 h before sampling commenced.The concentration of cortisol in plasma showed an ultradian rhythm with an amplitude of approximately 30 ng/ml and a frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

1988
1988
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…In diurnal animals, cortisol secretion is timed primarily by sleep-wake activities, with concentrations being highest in the early morning and lowest at night [Fulkerson et al, 1980;Thun et al, 1981;Czeisler and Klerman, 1999;Luboshitzky, 2000]. In both Asian and African elephants, nadir concentrations were observed from 2100 to 0500 hr, after which cortisol increased to a peak at about 0600 hr.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In diurnal animals, cortisol secretion is timed primarily by sleep-wake activities, with concentrations being highest in the early morning and lowest at night [Fulkerson et al, 1980;Thun et al, 1981;Czeisler and Klerman, 1999;Luboshitzky, 2000]. In both Asian and African elephants, nadir concentrations were observed from 2100 to 0500 hr, after which cortisol increased to a peak at about 0600 hr.…”
Section: Discussionmentioning
confidence: 94%
“…In other species, circulating cortisol secretion is dynamic and pulsatile, so it can be difficult to obtain an accurate measure of baseline through random sampling. Many also exhibit a diurnal pattern of cortisol secretion [Hudson et al, 1975;Fulkerson et al, 1980;Irvine and Alexander, 1994;Ingram et al, 1999], so timing of sample collection needs to be standardized.…”
Section: Introductionmentioning
confidence: 99%
“…When psychological stress is kept at a minimum, physiological reactions and endocrine changes are mostly related to the intensity of the thermal stress and the heat tolerance of the animals. There is a high variability in the basal cortisol levels among species, breeds and individuals of wild and domestic ungulates (Alvarez and Johnson 1971;Fulkerson et al 1980;Aganga et al 1990). In thermoneutral environments, cattle blood cortisol concentrations varies widely: 1,5-5, 9 μ.dl −1 ; 0,82-2,5 μ.dl −1 ; 1,0-1,6 μ.dl −1 (Ingraham et al 1976;Fulkerson et al 1980;Wise et al 1988 that the breed and individuals are the main source of variation.…”
Section: Discussionmentioning
confidence: 99%
“…In ruminants, contradictory reports exist about the presence of circadian rhythms in basal plasma cortisol concentrations. For example, in cattle several authors have reported a circadian rhythm in cortisol concentrations (Hays et al 1975, Fulkerson et al 1980, Thun et al 1981, Lefcourt et al 1993 whereas Hudson et al (1975) failed to detect any circadian rhythm. Such rhythms in cortisol concentrations have not been identified in white-tailed deer (Bubenik et al 1983), rusa deer (van Mourik & Stelmasiak 1984) or Eld's deer (Monfort et al 1993), although the existence of a circadian rhythm in the latter study could not be ruled out as the animals were blood sampled for only 10 h per day.…”
Section: Discussionmentioning
confidence: 99%